Ultrasonic Studies of Some Biomolecules in Aqueous Guanidine Hydrochloride Solutions at 298.15 K - R. Palani; A. Geetha; S. V. S. L. Poornima (E-Journal of Chemistry)
Ultrasonic velocity (U), viscocity (η) and density (ρ) of L - ascorbic acid, dextrose and sucrose in aqueous guanidine hydrochloride (0.3 m) have been measured at 298.15 K. The derived acoustical parameters namely adiabatic compressibility (β), apparent molal compressibility (ΨK) apparent molal volume (ΨV) limiting apparent molal compressibility (Ψ0K) limiting apparent molal volume (Ψ0V) and their constants (SK, Sv) and viscosity B- coefficient and hydration number (nH) have been computed from the experimental data. The variation of these parameters with respect to the molality of solutes have been explained on the basis of solute-solvent interaction and structure making tendency of the solutes in solvents.